Sleep and Daily Social Experiences as Potential Mechanisms Linking Social Integration to Nocturnal Blood Pressure Dipping. Issue 3 (24th April 2022) - Chin, Brian N.; Dickman, Kristina D.; Koffer, Rachel E.; Cohen, Sheldon; Hall, Martica H.; Kamarck, Thomas W.
ABSTRACT: Objective: Socially integrated individuals are at lower risk of cardiovascular disease morbidity and mortality compared with their more isolated counterparts. This association may be due, in part, to the effect of social integration on nocturnal blood pressure (BP) decline or "dipping, " a physiological process associated with decreased disease risk. However, the pathways linking social integration with nocturnal BP dipping are unknown. We sought to replicate the association between social integration and BP dipping, and to test whether sleep characteristics (duration, regularity, continuity) and/or daily social interactions (frequency, valence) helped to explain the association. Methods: A total of 391 healthy midlife adults completed an actigraphy assessment protocol that measured sleep. During four actigraphy assessment days, participants also completed ambulatory BP monitoring and ecological momentary assessment protocols that measured BP and social interactions at regular intervals throughout the day. Social integration was assessed via a questionnaire. Results: Linear regression controlling for age, sex, race, education, and body mass index indicated that higher levels of social integration were associated with greater nocturnal BP dipping, as indicated by a smaller ratio of night/day mean arterial pressure ( β = −0.11, p = .031). Analyses of indirect effects suggested that this association was explained, in part, by greater sleep regularity among more integrated individuals. We did not find evidence for other hypothesized indirect effects. Conclusions: This was the first study to investigate sleep and social mechanisms underlying the link between social integration and nocturnal BP dipping. Because sleep regularity is modifiable, this pathway represents a potential intervention target to promote nocturnal BP dipping.